Analysis of Dry Turning Process of AISI316 for Coated and Uncoated Insert Tools Based on Economical Method - Bagaber, Salem Abdullah; A. R., Yusoff (Universiti Malaysia Pahang, 2016)
Sustainability and clean of production are of importance in the machining processes where high energy amount is consumed. Reducing the power consumption during machining process can significantly improve the economical and environmental performance of manufacturing systems. The objective of this research is to evaluate the coated and uncoated carbide insert performance in hard turning process for AISI 316 in terms of power consumption, and tool wear. Economical method was study by developed a new cost modeling by integrated different cost estimation methods based on energy and tool life considerations. The performance of Coated Carbide and Uncoated Carbide tools were evaluated under dry turning process. The influence of cutting parameters of cutting speed, feed rate, and depth of cut analysis based on energy consumption and economical method. The optimum cutting condition that provide minimum consumed of energy was found at parameters, cutting speed (100 m/min), feed rate (0.15 mm/rev) and depth of cut (0.8mm). The study concluded that the out performance of uncoated carbide inserts can be implemented in hard turning applications and extreme cutting conditions can reduce of energy and saving machining cost.